The influence of pre- and post-zygotic barriers on interspecific Corymbia hybridization - Dickinson, Geoffrey R. (Oxford University Press, 2012)
BACKGROUND AND AIMS: Corymbia species from different sections hybridize readily, with some of increasing economic importance to plantation forestry. This study explores the locations of reproductive barriers between interspecific Corymbia hybrids and investigates the reproductive success of a wide taxonomic range of C. torelliana hybrid crosses. METHODS: Pollen, pistil and embryo development were investigated for four C. torelliana crosses (×C. torelliana, ×C. citriodora subsp. citriodora, ×C. tessellaris and ×C. intermedia) using fluorescent and standard microscopy to identify the locations of interspecific reproductive isolating barriers. Corymbia torelliana was also crossed with 16 taxa, representing six of the seven Corymbia sections, both Corymbia subgenera and one species each from the related genera, Angophora and Eucalyptus. All crosses were assessed for capsule and seed yields. KEY RESULTS: Interspecific C. torelliana hybridization was controlled by pre-zygotic reproductive isolating barriers inhibiting pollen adhesion to the stigma, pollen germination, pollen tube growth in the style and pollen tube penetration of the micropyle. Corymbia torelliana (subgenus Blakella, sect. Torellianae) was successfully hybridized with Corymbia species from subgenus Blakella, particularly C. citriodora subsp. citriodora, C. citriodora subsp. variegata, C. henryi (sect. Maculatae) and C. tessellaris (sect. Abbreviatae), and subgenus Corymbia, particularly C. clarksoniana and C. erythrophloia (sect. Septentrionales). Attempted intergeneric hybrids between C. torelliana and either Angophora floribunda or Eucalyptus pellita were unsuccessful. CONCLUSIONS: Corymbia hybrids were formed between species from different sections and subgenera, but not with species from the related genera Angophora or Eucalyptus. Reproductive isolation between the interspecific Corymbia hybrid crosses was controlled by early- and late-acting pre-zygotic isolating barriers, with reproductive success generally decreasing with increasing taxonomic distance between parent species. These findings support the monophyly of Corymbia and the close relationships of infrageneric clades. The hybridizing propensity of Corymbia species provides opportunities for breeding but suggests risks of environmental gene flow.